2021
DOI: 10.3390/atmos12081080
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Crop Management under Climate Uncertainty: Changing the Game for Sustainable Water Use

Abstract: Water supplies are projected to become increasingly scarce, driving farmers, energy producers, and urban dwellers towards an urgent and emerging need to improve the effectiveness and the efficiency of water use. Given that agricultural water use is the largest water consumer throughout the U.S. Southwest, this study sought to answer two specific research questions: (1) How does water consumption vary by crop type on a metropolitan spatial scale? (2) What is the impact of drought on agricultural water consumpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Abiotic stresses are hostile to plant growth and development. In particular, water deficiency is a severe constraint that affects growth and limits agricultural productivity on a global scale, a reason why several authors focused their attention on the optimization of strategies to ameliorate water deficit [43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…Abiotic stresses are hostile to plant growth and development. In particular, water deficiency is a severe constraint that affects growth and limits agricultural productivity on a global scale, a reason why several authors focused their attention on the optimization of strategies to ameliorate water deficit [43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…We use total ETa as a proxy for OWU because it often approximates consumptive water use, which refers to all the water consumed by plants or humans. The total ETa in summer has been demonstrated to be used to estimate the OWU at each pixel location (Kaplan et al., 2014; Myint et al., 2021; Singh et al., 2013). Gober et al.…”
Section: Methodsmentioning
confidence: 99%
“…We use total ETa as a proxy for OWU because it often approximates consumptive water use, which refers to all the water consumed by plants or humans. The total ETa in summer has been demonstrated to be used to estimate the OWU at each pixel location (Kaplan et al, 2014;Myint et al, 2021;Singh et al, 2013). Gober et al (2009Gober et al ( , 2012 has explored the correlation between observed water use and ET in Phoenix and presented a statistically significant relationship (R 2 = 0.89) for the 10 tracts (Gober et al, 2009(Gober et al, , 2012.…”
Section: Ecostress Data Processingmentioning
confidence: 99%
“…Drought is the most significant environmental stress in agriculture globally, and enhancing yield in water-limited environments is a primary goal of plant breeding [ 19 ]. Strategies such as developing and deploying drought-tolerant maize varieties are crucial in mitigating the detrimental effects of drought on agricultural productivity and livelihoods [ 20 ].…”
Section: Understanding Plant Responses To Drought Stressmentioning
confidence: 99%